INTERNET OF THINGS BASED ON WIRELESS SENSOR NETWORKS - Sandhya Kumari (International Journal of Multidisciplinary Research and Studies, 2020)
The introduction of those structures asks developers to choose from a vast range of gadgets, working modes, and architectural patterns, among other options. Regardless of the potential these technologies offer, the process of selecting is made more difficult by the wide variety of options available. Furthermore, there is a desire to optimize the implementation of those networks in a good way to ensure that the project of these packages can be run effectively. This group contains additionally secure users. Those nodes also work as a transmitter and a receiver, keeping the communication in both directions.